Recursive Compiling and Programming Environments (Summary) - Lamport, Leslie (1984)
This is an extended abstract I submitted to the 1995 POPL conference. (I never wrote the complete version.) It proposes the idea of recursive compiling, in which a program constructs a text string and calls the compiler to compile it in the context of the current program environment. Thus, a variable foo in the string is interpreted by the compiler to mean whatever foo means at the current point in the calling program. No one found the idea very compelling. When I discussed it with Eric Roberts, he argued that run-time linking would be a simpler way to provide the same functionality. I don't know if Java's reflection mechanism constitutes recursive compiling or just run-time linking.
Rejected from the 1985 POPL Conference